Analysis of Heavy Equipment Management Based on Cost and Time Values in the Local Road Improvement Project Package 6 - Rachman, Tezar Aulia; Firdaus, Muhammad (Fakultas Teknik Universitas Tanjungpura, 2024)
Heavy equipment is crucial in construction, significantly impacting the optimization of time and cost efficiency, particularly in road construction projects. This research involves analyzing data on the heavy equipment used, calculating productivity, and determining the most effective and efficient combination of heavy equipment using the trial and error analysis method. From the analysis of cost and time productivity in the implementation of the aggregate foundation layer work, the productivity of heavy equipment was measured at two locations. At Jl. RT.040, the productivity rates were: Dump Truck at 5.27 m ³/hour, Motor Grader at 16.20 m ³/hour, Vibratory Roller at 14.58 m ³/hour, Wheel Loader at 174.96 m ³/hour, and Water Tanker at 16.20 m ³/hour. At Jl. Komp. Agis, the productivity rates were: Dump Truck at 4.58 m ³/hour, Motor Grader at 16.20 m ³/hour, Vibratory Roller at 14.58 m ³/hour, Wheel Loader at 174.96 m ³/hour, and Water Tanker at 16.20 m ³/hour. Subsequent data processing aimed to determine the optimal combination of heavy equipment in terms of cost and time using the trial and error analysis method. The results showed that the original condition lasted 217 hours for Rp. 134,286,351.00. Alternative 1 had a duration of 157 hours for Rp. 109,094,993.00, and Alternative 2 had a duration of 124 hours for Rp. 123,202,383.00.Keywords: LRIP Package 6, Cost and time values, Heavy Equipment Management, Calculating productivity, Determining the most effective